Implementation of quality improvement coaching versus physician communication training for improving human papillomavirus vaccination in primary care: a randomized implementation trial. Issue 1 (9th July 2021) - Grabert, Brigid K; Kurtzman, Rachel; Heisler-MacKinnon, Jennifer; Leeman, Jennifer; Bjork, Adam; Kameny, Maddy; Liu, Amy; Todd, Karen; Alton Dailey, Susan; Smith, Kevin; Brewer, Noel T; Gilkey, Melissa B
Lay Summary: Our cluster randomized trial compared two interventions that health departments commonly use to increase HPV vaccination coverage: quality improvement (QI) coaching and physician communication training. We found that QI coaching cost less and was more often adopted by primary care clinics, but communication training reached more staff members per clinic, including vaccine prescribers. Findings provide health departments with data needed to weigh the implementation strengths and challenges of QI coaching and physician communication training for increasing HPV vaccination coverage. Abstract: Many US health departments (HDs) conduct in-person quality improvement (QI) coaching to help primary care clinics improve their HPV vaccine delivery systems and communication. Some HDs additionally conduct remote communication training to help vaccine prescribers recommend HPV vaccination more effectively. Our aim was to compare QI coaching and communication training on key implementation outcomes. In a cluster randomized trial, we offered 855 primary care clinics: 1) QI coaching; 2) communication training; or 3) both interventions combined. In each trial arm, we assessed adoption (proportion of clinics receiving the intervention), contacts per clinic (mean number of contacts needed for one clinic to adopt intervention), reach (median number of participants per clinic), and delivery cost (mean cost per clinic) from the HD perspective. More clinics adopted QI coaching than communication training or the combined intervention (63% vs 16% and 12%, both p < .05). QI coaching required fewer contacts per clinic than communication training or the combined intervention (mean = 4.7 vs 29.0 and 40.4, both p < .05). Communication training and the combined intervention reached more total staff per clinic than QI coaching (median= 5 and 5 vs 2, both p < .05), including more prescribers (2 and 2 vs 0, both p < .05). QI coaching cost $439 per adopting clinic on average, including follow up ($129/clinic), preparation ($73/clinic), and travel ($69/clinic). Communication training cost $1, 287 per adopting clinic, with most cost incurred from recruitment ($653/clinic). QI coaching was lower cost and had higher adoption, but communication training achieved higher reach, including to influential vaccine prescribers.